EAnalytics: Dynamic Web-based Analytics for the Energy Industry. Issue 1 (30th November 2016) - Govan, Paul
EAnalytics is a web application built on top of R that provides dynamic data analytics to energy industry stakeholders. The application allows users to dynamically manipulate chart data and style through the Shiny package's reactive framework. eAnalytics currently supports a number of features including interactive datatables, dynamic charting capabilities, and the ability to save, download, or export information for further use. Going forward, the goal for this project is that it will serve as a research hub for discovering new relationships in the data. The application is illustrated with a simple tutorial of the user interface design.